Needs Analysis of English Materials for Islamic Economics Students - Solehan Solehan; Alamsyah Harahap; Irma Diani (Association of Language Teachers in Southeast Asia (ALTSA), 2021)
This study aims to find out the needs of English material for Islamic economics students. The method employed in this research is descriptive. Forty students and ten stakeholders were asked to complete the questionnaire, and ten stakeholders were interviewed. The result of the research: 1) the highest themes or topics needed based on students' perception is the relevance of Islamic economics, meanwhile based stakeholders' perception is the methodology of Islamic economics; 2) the highest discourse texts needed based on students' perception is Islam as a way of life, whereas based on stakeholders' perception is facts and theories of Islamic economics; and 3) the highest English Skills needed to be based on students and stakeholders' perception is speaking skill. In sum, the researchers concluded that speaking is an important skill needed by the Islamic economics study program of the Muhammadiyah University of Bengkulu.